Reinterpreting the development of reading skills - PARIS, SCOTT G. (Reading research quarterly, 2005)
Theories about reading have neglected basic differences in the developmental trajectories of skills related to reading. This essay proposes that some reading skills, such as learning the letters of the alphabet, are constrained to small sets of knowledge that are mastered in relatively brief periods of development. In contrast, other skills, such as vocabulary, are unconstrained by the knowledge to be acquired or the duration of learning. The conceptual, developmental, and methodological constraints on different rea ing skills are described in this essay that identifies various types of constraints on reading constructs and measures. Examples of reading research and assessment are discussed to illustrate (a) how the constraints can help to explain transitory correlational patterns among reading data, (b) how proxy effects surrounding constrained skills influence interpretations of reading development, (c) how prescriptions to teach constrained skills are causal misinterpretations of longitudinal correlations, and (d) why interventions on constrained skills usually lead only to temporary gains on skills aligned with the constrained skill. Because constrained skills are not normally distributed conceptually or empirically, except on special occasions, analyses based on parametric statistics are inappropriate. This essay describes implications for theories of reading development, research methods, and educational policies. /// [Spanish] Las teorías acerca de la lectura han descuidado diferencias básicas en el camino evolutivo de las habilidades relacionadas con la lectura. Este ensayo propone que ciertas habilidades de lectura, como el aprendizaje de las letras del alfabeto, estin restringidas a pequeüos conjuntos de conocimientos cuyo dominio se concreta en periodos relativamente breves. En contraste, otras habilidades tales como el vocabulario, no estin restringidas por el conocimientoque se adquiriri ni por la duración del aprendizaje. En este ensayo se describen las restricciones conceptuales, evolutivas y metodológicas en diferentes habilidades de lectura; el mismo identifica varios tipos de restricciones en las conceptualizaciones sobre la lectura y en las medidas de lectura. Se discuten ejemplos de investigación y evaluación en lectura para ilustrar: a) de qué modo las restricciones pueden ayudar a explicar patrones correlacionales transitorios entre los datos de lectura, b) cómo efectos secundarios próximos a las habilidades restringidas influencian las interpretaciones del desarrollo en lectura, c) cómo ciertas propuestas para enseñar habilidades restringidas son malas interpretaciones causales de correlaciones longitudinales y d) por qué las intervenciones sobre las habilidades restringidas generalmente conducen sólo a logros temporarios en habilidades afines a la habilidad restringida. Debido a que las habilidades restringidas, excepro en ocasiones especiales, no están normalmenre distribuidas conceptual o empíricamente, son inapropiados los análisis hasados en la estadistica paramétrica. El ensayo describe implicancias para las teorías del desarrollo lector, los métodos de investigación y las políticas educativas. /// [German] Theorien übers Lesen haben die grundsaalichen Unterschiede in den auk Lesen bezogenen sich entwickeinden Leistungsbahnen vernachlissigt. Dieser Aufsatz vertritt die Ansicht, daß einige Leseleistungen, wie beispielsweise das Erlernen der Buchstaben des Alphabets, auf eng begrenzte Erkenntniswerte beschrankt sind, die in relativ kurzen Entwicklungsperioden beherrscht werden. Im Gegensatz dazu sind andere Kenntnisse, wie das Vokabular, unhegrenzt im zu erlernenden Wissen oder in der Dauer beim Lernen. Die konzeptualen, entwicklungsbedingten und methodologischen Beschrankungen auf unterschiedliche Leseleistungen werden in diesem Aufsatz beschrieben, welcher verschiedene Typen von Einschrankungen im Lesen von Wortfügungen und Abschätzungen identifiziert. Beispiele aus der Leseforschung und Bewertung werden diskutiert, um zu illustrieren, (a) wie die Einschränkungen dazu verhelfen können, transitorische Korrelationsmuster zwischen den Lesedaten zu erklären, (b) wie Vertret~n~sfunktionenu mgebende Auswertungen von Leistungseinwirkungen der Leseentwicklung beeinflußt, (c) wie Verordnungen zum Unterrichten eingegrenzter Kenntnisse kausale Fehlinterpretationen der lngenkorrelationen sind, und (d) warum Interventionen bei eingegrenzten Kenntnissen meistens nur zu zeitweisen Fortschritten der angeglichenen Leistungen eingeschrankter Fähigkeiten führen. Da eingeschränkte Befähigungen normalenveise nicht konzeptionell oder empirisch eingeteilt sind, außer bei speziellen Anlässen, sind die auf parametrische Statistiken basierte Analysen ungeeignet. Dieser Aufsatz beschreibt Implikationen für Theorien zur Leseentwicklung, Forschungsmethoden und Unterrichtsverfahren. /// [Japanese] 読みの理論は、読み に関連する技術の発 達上の軌道における 基本的な違いを無視 してきた。本稿 では、アルフアべッ トの文字の学習のよ うな読みの技術は、 比較的短い発達の時 期に身に付く小 知識に制約されてい ると提唱する。対照 的に、語業のような 他の技術は、習得さ れる知識や学習 の期間によって制約 されない。様々な読 みの技術に対する概 念的、発達的、方法 論的制約が、読 みの構成概念及び測 定数に対する様々な 制約を識別する本稿 において叙述される 。(a) どのよ うにそうした制約が 読みのデータの一時 的な相関パターンを 説明するのに役立つ のか、(b) ど のように制約された 技術を取り囲む代理 効果が読みの発達の 解釈に影響を与えて いるのか、 (c) どのように制約さ れた技術を教えるた めの規定が、縦断的 相関の因果関係の間 違った解釈 であるのか、(d) な ぜ制約された技術へ の介入が、大抵の場 合、制約された技術 と連結した技 術の一時的な伸びに しか至らないのかを 説明するために、読 みの研究と評価の例 を論じる。制約 された技術は、特別 な場合を除いて、概 念的にも経験的にも 正規分布されないた め、パラメトリ ック検定による分析 は不適当である。本 稿は、読みの発達理 論、研究方法、そし て教育方針のた めの示唆を述べる。 /// [French] Les théories de la lecture ont négligé des différences de base dans lcs trajectoires du développement des conlpétences relatives à la lecture. Cet essai énonce que certaines compitences de lecture telles que les lettres de l'alphabet se réduisent à de petirs ensembles de connaissances qui sont maîtrisées au cours de périodes de développement relativement brkves. Par contre, d'autres compétences telles que le vocabulaire ne sont pas limitées par lcs connaissances à acquérir ou par la durée de l'apprentissage. On décrit dans cet essai, qui identifie différents types de contraintes sur les constructs et les évaluatiolls de la lecture, les contraintes conceptuelles, développementales, et méthodologiques de différentes compétences de lecture. On discute des exemples de recherche et d'évaluation de la lecture afin de montrer a) comment les contraintes peuvent aider à expliquer certains patrons provisoires de correlations entre résultats de lecture, b) comment des effets voisins qui se trouvcnt autour des compétences réduites jouent un rô1e sur les interprétations du développement de la lecture, c) comment les prescriptions d'enseignement de compétences réduites sont responsables d'erreurs d'interprétation des corrélations longitudinales et, d) pourquoi des interventions sur des compétences réduites ne conduisent en général qu'à d es gains temporaires sur des compétences liées à celles-ci. Du fait que, sauf en de rares occasions, les compétences réduites ne sont pas distribuées normalement, rant conceptuellement qu'empiriquement, les analyses reposant sur des statisciques paramétdques sont inappropriées. Cet essai énonce enfin des implications sur les théories du développement de la lecture, les m'ðhodes de recherche, et lcs politiques éducatives. /// [Russian] Теории чтения пренебрегают тем фактом, чт о инАивиАуаΛьные траектории развития навыков, тем иΛи иным образом связанных с чтением, весьма разΛичны. Некоторые из этих навыков например освоение букв аΛфавита, автор преАΛагает препоАавать компактно в виАе Аостаточно ограниченного бΛока знаний, освоить которые преАΛагается за относитеΛьно краткий срок. Напротив, Аругие навыки такие как, к примеру, испоΛьзование и расширение сΛоварного запаса, не АоΛжны быть жесто вписаны в опреАеΛенный б Λок знаний иΛи еАиницу времени, отвеАенную АΛя их освоения. В статье кΛассифицированы концептуаΛьные, метоАические и инАивиАуаΛьные параметры и огранчения, вΛияющие на развитие навыков чтения. ПривоАятся примеры иссАеΛований самого чтения и его оценивания, чтобы проиΛΛыстрировать, (a) что знание о цринуАитеΛьном разьитии наьыкоь может цомочь в ьыяьΛении и трактовке временных и непрочных резуΛьтатов, (б) что промежуточные резуΛьтаты, поΛученные в резуΛьтате принуАитеΛьного развития навыков, вΛияют на интерпретацию поΛученных Аанных, (B) что рекоменАации по принуАитеΛьному развитию навыков возникают в резуΛьтате неверноао истоΛкования кратковременных корреΛяций как АоΛговременных и (г) что принуАитеΛьное развитие навыков обычно веАет тоΛько к временным Аостиженигм во всем, что связано с этими навыками. ПоскоΛьку навгзанные навыки крайне реАко развиваются концептуаΛьно иΛи эмпирически, анаΛиз, основанный на параметрической статитике зАесь неприемΛем. ПреАΛагаются вывоАы, связанные с теорий развития навыков чтения, метоАов иссΛеАования чтения и образоватеΛьной поΛитикой.